(untitled) (Web of Teachers: Inderscience Research, 2025)
Improving the scientific and methodological foundations of teaching Karakalpak literature at schools and the principles of compiling textbooks, improving methodological issues using problematic, monographic, review texts based on the materials presented in the Karakalpak literary program, lecture classes and teaching methods. He mechanism of using interactive methods in modern lessons has been improved; it has been strengthened by teacher motivation based on the needs of teachers, using effective problem-solving situations in teaching Karakalpak literature and activating the communicative process.